Causes of corporate crisis: an investigation on Smes to support the learning process - Sgrò, Francesca; Palazzi, Federica; Ciambotti, Massimo; Gabbianelli, Linda (Piccola Impresa / Small Business, 2022)
The study allows us to reflect on the leading (internal and external) causes of the crisis for SMEs also considered the corporate age, useful to identify the critical areas that require intervention to prevent or mitigate the crisis. A questionnaire was administered to the bankruptcy trustees appointed by juridical authority to manage 228 bankruptcy procedures. Descriptive statistical analysis and principal component analysis had been employed. Data shows that economic and industrial crisis, market factors and credits management (as external determinants) and planning activities, corporate financial policies, governance, and ownership issues (as internal factors) are recognized as critical of a firm bankruptcy procedure activation. The main limit concerns the restricted sample size due to challenges in the data gathering process considering the “bankruptcy status” and the reference context, characterized by small-sized enterprises, by hilly and mountain landscape, not easy to reach, with infrastructures not so much developed.